Enhanced stability and optical performance of MAPbI3 perovskite films through B4PBF4 ionic liquid integration: A route to durable photovoltaics - Edgar González-Juárez; Ana I. Santiago-Mustafat; Miguel A. Amado-Briseño; Daniel A. Acuña-Leal; Eduardo M. Sánchez-Cervantes; Arián Espinosa- Roa (Journal of Ionic Liquids)
An ionic liquid (B4PBF4) was synthesized and characterized using spectroscopic techniques, incorporating it in different proportions (0.25, 0.5, and 1.5 % w/w) into thin perovskite films. The results show that 1.5 % concentration significantly improves the optical properties by minimizing trap states and preventing charge recombination. XPS analysis indicates a strong interaction between the ionic liquid and lead halides at this proportion. Additionally, photovoltaic devices fabricated with this percentage achieved higher efficiency. In terms of stability, the 1.5 % also prevented water absorption on the surface, delaying film degradation up to 500 h.